Assessing Response to Radiation Therapy Treatment of Bone Metastases: Short-Term Followup of Radiation Therapy Treatment of Bone Metastases with Diffusion-Weighted Magnetic Resonance Imaging. (26th March 2014) - Cappabianca, Salvatore; Capasso, Raffaella; Urraro, Fabrizio; Izzo, Andrea; Raucci, Antonio; Di Franco, Rossella; Rotondo, Antonio
Abstract : This study examined the usefulness of diffusion-weighted (DW) Magnetic Resonance Imaging (MRI) in monitoring bone metastases response to radiation therapy in 15 oligometastatic patients. For each metastasis, both mean apparent diffusion coefficient (ADC) changes and high b -value DW metastasis/muscle signal intensity ratio (SIR) variations were evaluated at 30 ± 5 days and 60 ± 7 days after the end of treatment. On baseline DW-MRI, all bone metastases were hyperintense and had signal intensities higher than normal bone marrow on calculated ADC maps. At follow-up evaluations, 4 patterns of response were identified: (I) decreased high b -value DW SIR associated with increased mean ADC (83.3% of cases); (II) increased mean ADC with no change of high b -value DW SIR (10% of cases); (III) decreased both high b -value DW SIR and mean ADC (3.3% of cases); (IV) a reduction in mean ADC associated with an increase in high b -value DW SIR compared to pretreatment values (3.3% of cases). Patterns (I) and (II) suggested a good response to therapy; pattern (III) was classified as indeterminate, while pattern (IV) was suggestive of disease progression. This pattern approach may represent a useful tool in the differentiation between treatment-induced necrosis and highly cellular residual tumor.